Dampak Media Pembelajaran Cerita Bergambar Berbasis Budaya Sunda Terhadap Peningkatan Keterampilan Menulis Narasi Siswa Sekolah Dasar Di Purwakarta - Tati Sulastri; Yudi Bachtiar; Ihsan Rizali (STKIP Subang, 2026)
The impact of picture story learning media based on Sundanese culture on improving narrative writing skills of elementary school students in Purwakarta ABSTRACT This study aims to determine the impact of using Sundanese culture-based picture story learning media on improving elementary school students' narrative writing skills. This research was motivated by students' difficulties in developing ideas, organizing story sequences, and expressing thoughts into coherent narrative texts. The study employed a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Design. The research was conducted at SDN 3 Panyindangan, Sukatani District, Purwakarta Regency, involving 50 fourth-grade students consisting of an experimental class and a control class, with 25 students in each class. The research instruments were narrative writing skill tests in the form of pretests and posttests, supported by documentation. The data were analyzed using statistical tests, including prerequisite tests, hypothesis testing, and N-Gain analysis. The results showed that the use of Sundanese culture-based picture story learning media had a significant impact on improving students' narrative writing skills. This was evidenced by the hypothesis test result with a significance value of 0.000 < 0.05 and the higher N-Gain score obtained by the experimental class compared to the control class. Therefore, Sundanese culture-based picture story learning media is effective as an alternative medium for Indonesian language learning to improve elementary school students' narrative writing skills.